Photocatalysis from a series of polyoxoazocobaltate high-nuclearity nanoclusters. Issue 15 (29th January 2016) - Mu, Bao; Wang, Qing; Huang, Ru-Dan
Abstract : By changing the substituent groups of mercapto-based ligands, polyoxoazocobaltate high-nuclearity nanoclusters have been synthesized and structurally characterized, and they display photocatalytic activities for degradation of organic dyes. Abstract : Three Co20 nanoclusters possessing photocatalytic activity, namely, [Co20 (OH)24 (MMT)12 (SO4 )](NO3 )2 ·6H2 O (1 ), [Co20 (MT)12 (μ3 -OH)23 (μ3 -O)(SO4 )(CH3 O)]·2EtOH (2 ) and [Co20 (AMT)11 (MT)(μ3 -OH)22 (μ3 -O)2 (SO4 )(H2 O)]·EtOH·4H2 O (3 ) (MMT = 2-mercapto-5-methyl-1, 3, 4-thiadiazole, MT = 2-mercapto-1, 3, 4-thiadiazole, AMT = amino-5-mercapto-1, 3, 4-thiaoldiaze and EtOH = ethanol) have been obtained under hydrothermal conditions. Compound1 presents a homometallic Co II cluster containing the α-Keggin polyoxometalate structure. Compound2 features a cobalt cluster including the α-Keggin-type polyoxoazocobaltate Co12 core, capped by seven octahedral Co II ions and one square-pyramidal Co II ion. Different from compounds1 and2, compound3 possesses the semi-open square-pyramidal-based Co10 core, and ten octahedral Co II ions are distributed around the core cluster. Through the comparison from structures of compound1 and compounds2–3, the different substituent groups of the organic ligands play an important role in the formation of the final homometallic Co II clusters. The electrochemical behaviors of the title compounds at room temperature have been investigated. Moreover, the high-nuclearity metal clusters are firstly acted as photocatalysts to be researched, and then the photocatalytic properties show that compounds1–3 as the potential photoactive materials have the selectivity for degradation of some organic dyes.